The role of extracellular histones in systemic-onset juvenile idiopathic arthritis - Xiao Hu; Qiuling Xie; Xi Mo; Yanliang Jin (BMC, 2019)
Abstract Background To explore the effects of extracellular histones released by activated neutrophils on systemic-onset juvenile idiopathic arthritis (SoJIA), and to study the change of serum histone level between the active and remissive stage of SoJIA, then to clarify the role of serum histone in the pathogenesis of SoJIA. Methods Twenty-six patients with SoJIA were recruited, and clinical informations were collected, and the serum histone was detected by ELISA. While neutrophils from normal children were incubated with the serum from the patients with SoJIA, also including incubated with FeCL3 and histone, the extracellular histone was detected, respectively; heparin was added to the above-mentioned groups to observe the changes of extracellular histone levels. The proportions of neutrophils, which released NETs, were calculated by confocal microscope. Results The levels of serum histones in active SoJIA group (0.90 ± 0.90) were significantly higher than in remissive SoJIA group (0.17 ± 0.10) (P = 0.0009), and also higher than in control group (0.14 ± 0.09) (P = 0.246). Histone affects on clinical manifestations (including fever, rash, joint pain, liver and spleen enlargement, and serositis), except for joint pain. The proportions of neutrophils releasing NETs, that neutrophils were incubated with the serum from active SoJIA group, were 31.93% significantly higher than 12.32% from remissive SoJIA group (P < 0.0001). The proportions of neutrophils releasing NETs, that neutrophils were incubated with different concentration FeCl3 or with different concentration histones respectively, were positively correlated with the concentration of incubation; while heparins were added, NETs from neutrophils could be reduced effectively. Conclusions The level of serum histone is positively correlated with the activity of SoJIA. Serum histone may be from NETs, which were released by activated neutrophils. Free iron can activate neutrophils to produce NETs, which may release histones, and histones can further promote NETs to be released, that results in a positive feedback loop of histones, and that may be one of the pathogenesis of acute SoJIA or MAS secondary to SoJIA. Histones maybe play one of important roles in the pathogenesis of SoJIA. Heparin can act on histones to prevent histone-induced inflammation. Trial registration ChiCTR-OOC-15006228. Registered 9 April 2015, http://www.chictr.org.cn/showproj.aspx?proj=10752